Promoting Innovation in Developing Countries : A Conceptual Framework - Aubert, Jean-Eric (World Bank, Washington, DC, 2012)
The author provides a conceptual framework for approaching the promotion of technological innovation and its diffusion in developing countries. Innovation climates in developing countries are, by nature, problematic, characterized by poor business and governance conditions, low educational levels, and mediocre infrastructure. This raises particular challenges for the promotion of innovation. The latter should be understood as the diffusion of technologies-and related practices-which are new to a given context (not in absolute terms). What matters first is to provide the necessary package of support-technical, financial, commercial, legal, and so on-with flexible, autonomous agencies adapting their support and operations to the different types of concerned enterprises. Facilitating and responding to the emergence of grass-root needs at the local level is also essential. Support to entrepreneurs and local communities should be primarily provided in matching grant forms to facilitate the mobilization of local resources and ownership. It is of primary importance to pay the greatest attention to country specificities, not only in terms of development level, size, and specialization, but also in terms of administrative and cultural traditions. At the global level, major issues need also to be considered and dealt with by appropriate incentives and regulations: the role of foreign direct investment in developing countries' technological development, conditions of technologies' patenting and licensing, the North-South research asymmetry, and brain drain trends.